Correlações entre propriedades dinâmico-mecânicas e durabilidade sob fadiga mecânica em compósitos de polipropileno/polipropileno maleificado/fibra de vidro - Cruz, Michelle Christina Avezum da (Universidade Federal de São Carlos, 2006)
Although the influence of interfacial adhesion on short-term mechanical performance of fiber-reinforced thermoplastic composites has been well established, very little published information is available on the influence of the composite interface/interphase characteristics on fatigue properties of these materials. Fatigue life determination is of paramount importance for engineering applications of injection moulded short glass fiber (GF) reinforced polypropylene (PP) composites. Thus, this work is related to an investigation on the influence of maleated polypropylene (PP-g-MAH) interfacial compatibilizer on the fatigue resistance properties of 30 percent GF-reinforced PP composites. The mechanical fatigue analysis was carried out using four-point bending tests under deformation controlled mode at frequencies of 1 Hz and complete reverse cycle (R = - 1). In order to obtain quick comparative data on PP-g-MAH compatibilizer performance on the fatigue life of these composites, an experimental procedure was elaborated in order to correlate the properties determined by dynamicmechanical thermal analysis (DMTA) of composite samples, both pristine or subjected to short-term cyclic loading, with the experimentally determined fatigue life of these materials. The main conclusions of this work indicate that the mechanical damping (tan d) values, related to the fiber-polymer interfacial friction, reduce with compatibilizer content; this effect being better evidenced in the fatigued samples. The decrease in tan d values with compatibilizer content clearly indicate an increase in the composite interfacial compatibility and were found to be inversely proportional to the number of cycles to failure determined by long-term fatigue testing, thus, promoting an increase in the fatigue life of the investigated PP/PP-g-MAH/30%GF composites.
Keywords: Compósitos poliméricos; Durabilidade; Fadiga mecânica; Propriedades mecânicas; Compatibilizante interfacial; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA